Water Storage Decisions and Consumptive Use May Constrain Ecosystem Management under Severe Sustained Drought. (8th June 2022) - Bruckerhoff, Lindsey A.; Wheeler, Kevin; Dibble, Kimberly L.; Mihalevich, Bryce A.; Neilson, Bethany T.; Wang, Jian; Yackulic, Charles B.; Schmidt, John C.
Abstract: Drought has impacted the Colorado River basin for the past 20 years and is predicted to continue. In response, decisions about how much water should be stored in large reservoirs and how much water can be consumptively used will be necessary. These decisions have the potential to limit riverine ecosystem management options through the effect water‐supply decisions have on reservoir elevations. We used projected hydrology and river temperatures to compare the outcome of combinations of water storage scenarios and consumptive use limits on metrics associated with ecosystem management of the Colorado River in Grand Canyon. Ecosystem management metrics included the ability to implement designer flows, temperature suitability for fishes, and fragmentation. We compared current water management operations to prioritizing storage in either Lake Mead or Lake Powell combined with three levels of consumptive use. Projected reservoir levels limited environmental flow delivery and increased fragmentation regardless of where water was stored if consumptive use was not limited. Warmer river temperatures associated with low reservoir levels are likely, creating suitable conditions for non‐native species of concern, such as smallmouth bass. Water storage decisions provided variability and management flexibility, but water storage was less important when less water was available, highlighting the importance of keeping water in the system to provide flexibility for achieving ecosystem goals.